2015
DOI: 10.1136/bcr-2015-211371
|View full text |Cite
|
Sign up to set email alerts
|

Pradaxa-induced esophageal ulcer

Abstract: Pradaxa (dabigatran) is a direct thrombin inhibitor approved for prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation. We describe a case of esophageal ulceration associated with Pradaxa administration in a 75-year-old man. The patient reported difficulty swallowing and a burning sensation after taking his first dose of Pradaxa. An esophagogastroduodenoscopy (EGD) revealed linear ulcerations in the mid-esophagus. Pradaxa was held beginning the day before the EGD. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
7
1
1
Order By: Relevance
“…In a cytotoxicity study, although the study design and test concentrations of dabigatran were different from our study, no cytotoxic effect was shown with dabigatran and degradation products (24). In a real-life setting and clinical practice, mid-esophageal ulcer was reported in some of the patients using dabigatran, suggesting that dabigatran has a direct caustic effect on capsular formation (25,26). In the present study, although warfarin showed similar fi broblastic morphology with the control group, except for dilution I, cell viability was found to be statistically signifi cantly lower in all dilutions, compared to the control group.…”
Section: Assessment Of Cell Viabilitycontrasting
confidence: 69%
“…In a cytotoxicity study, although the study design and test concentrations of dabigatran were different from our study, no cytotoxic effect was shown with dabigatran and degradation products (24). In a real-life setting and clinical practice, mid-esophageal ulcer was reported in some of the patients using dabigatran, suggesting that dabigatran has a direct caustic effect on capsular formation (25,26). In the present study, although warfarin showed similar fi broblastic morphology with the control group, except for dilution I, cell viability was found to be statistically signifi cantly lower in all dilutions, compared to the control group.…”
Section: Assessment Of Cell Viabilitycontrasting
confidence: 69%
“…Furthermore, an acidifying agent was added to the reference formulation to acidify the solid‐liquid interface and surrounding microenvironment, maintaining a favorable pH condition, improving the apparent solubility, intestinal dissolution of the drug, and ultimately favoring intraluminal supersaturation, which may improve intestinal absorption. The caveat of using acidifying agents is to cause esophageal ulcer and dyspepsia 5,37,38 …”
Section: Discussionmentioning
confidence: 99%
“…The caveat of using acidifying agents is to cause esophageal ulcer and dyspepsia. 5,37,38 In this research, PSAs were performed on both CSR and PRC as substitute of presence and absence of acidifying and enteric coating agents, respectively. CSR is the ratio between maximum solubility attainable kinetically (critical supersaturation concentration [CSC]) and equilibrium solubility (S eq ).…”
Section: Dabe Dosing Regimenmentioning
confidence: 99%
“…The rate of esophageal bleeding was significantly higher in the antithrombotic group (12/99, 12.1% versus 6/131, 4.6%) for Bezold-Jarisch reflection (induced by hypovolemia and myocardial ischemia during or after cardiac surgery and percutaneous coronary intervention) [10,11]. In addition, antithrombotic drugs reportedly induce esophageal ulcers (taking antithrombotic drugs in the recumbent position and/or insufficient water consumption, leading to drug retention and damage to the esophagus) [12][13][14].…”
Section: Discussionmentioning
confidence: 99%